2017
DOI: 10.21859/cej-030910
|View full text |Cite
|
Sign up to set email alerts
|

Status and Challenges of Medical Waste Management in Hospitals of Iran

Abstract: Medical waste is of great importance due to its hazardous nature that can cause undesirable effects on humans and the environment. This study focuses on medical waste management in hospitals of Iran. Data were collected based on questionnaires and for self-report of medical waste management. The results along with other information were sent to the ministry of health network system. Results indicated that the mean generation rate of non-hazardous and sharp and infectious and total wastes in Iran were, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 26 publications
2
17
1
1
Order By: Relevance
“…Approximately 37.9% of the total wastes generated at Tehran's hospitals were infectious before the COVID-19 pandemic, which is significantly greater than WHO estimated value for hospitals (< 15%). Insufficient programs on separation of hospital wastes has increased the generation rate of infectious wastes and associated treat [15,16]. Medical wastes collected from Tehran's hospitals varied between 52 and 74 tonnes per day from March 2019 to January 2020, with an average of 68 tonnes per day.…”
Section: Hospital Waste Management In Tehran During the Covid-19 Pandmentioning
confidence: 99%
“…Approximately 37.9% of the total wastes generated at Tehran's hospitals were infectious before the COVID-19 pandemic, which is significantly greater than WHO estimated value for hospitals (< 15%). Insufficient programs on separation of hospital wastes has increased the generation rate of infectious wastes and associated treat [15,16]. Medical wastes collected from Tehran's hospitals varied between 52 and 74 tonnes per day from March 2019 to January 2020, with an average of 68 tonnes per day.…”
Section: Hospital Waste Management In Tehran During the Covid-19 Pandmentioning
confidence: 99%
“…Although the results of the current study showed a generation rate (0.5 kg/(bed•day)) that represents a very small number of medical facilities in Iraq, the overall generation rate of medical wastes based on the number of state-owned hospitals in Iraq could range from 3.8 to 4.2 kg/(bed•day) [3]. This amount is higher than the range of 0.6-3.7 kg/(bed•day), which was reported by several studies in other countries in the Middle East region [5,[12][13][14][15]. The Iraqi Ministry of Health and Environment has put general guidelines for hospitals to manage their medical waste.…”
Section: Discussionmentioning
confidence: 97%
“…High rate of infectious waste might be due to different factors for instance improper infectious waste segregation, less training programs and lack of planning. Infectious waste treatment and disposal cost significantly can be reduced by implementing the educational programs and proper planning of waste minimization [27]. To enhance segregation efficiency and reduce inappropriate use of containers, the containers should be placed at proper place and labeled carefully [28].…”
Section: Discussionmentioning
confidence: 99%
“…Sanida et al (2010) used these statistical analyses to evaluate relationship of number of beds, out-patient, accidents and emergency patients, infectious and general waste with total waste. In addition, Eslami et al (2017) used Pearson correlation coefficient and concluded that there was significance difference among private and governmental hospitals, with reference of infectious and sharp waste generation rates (P=0.027). Significant differences between specialized and general hospitals were also showed in group of non-hazardous waste (P=0.039), infectious waste (P=0.001) and total waste generation rate (P=0.02).…”
Section: Discussionmentioning
confidence: 99%